Atom probe study of chromium oxide spinels formed during intergranular corrosion - La Fontaine, Alexandre; Yen, Hung-Wei; Felfer, Peter; Ringer, Simon P.; Cairney, Julie M. (Scripta Materialia, 2015)
Atom probe microscopy has been used to study the inhomogeneous nature of chromium oxide spinels in intergranular corrosion of a 253 MA austenitic stainless steel after thermal cycling up to 970 °C in air. The results indicate that the non-continuous character of the spinel layers originates from nanoscale phases such as iron-rich oxides along the chromite grain boundaries and silicate particles. Their role in the rate of intergranular corrosion is discusse
Keywords: Atom probe tomography; Chromium oxide spinels; Corrosion; Oxidation; Stainless steel